RF MEMS circuit design for wireless communications - Santos, Héctor J. de los (Microelectromechanical systems series., 2002)
This is the first comprehensive book to address the design of RF MEMS-based circuits for use in high performance wireless systems. A groundbreaking research and reference tool, the book enables you to understand the realm of applications of RF MEMS technology; become knowledgeable of the wide variety and performance levels of RF MEMS devices; and partition the architecture of wireless systems to achieve greater levels of performance. This innovative resource also guides you through the design process of RF MEMS-based circuits, and establishes a practical knowledge base for the design of high-yield RF MEMS-based circuits.